Engineering Single‐Atom Cobalt Catalysts toward Improved Electrocatalysis. Issue 15 (5th March 2018) - Wan, Gang; Yu, Pengfei; Chen, Hangrong; Wen, Jianguo; Sun, Cheng‐jun; Zhou, Hua; Zhang, Nian; Li, Qianru; Zhao, Wanpeng; Xie, Bing; Li, Tao; Shi, Jianlin
Abstract: The development of cost‐effective catalysts to replace noble metal is attracting increasing interests in many fields of catalysis and energy, and intensive efforts are focused on the integration of transition‐metal sites in carbon as noble‐metal‐free candidates. Recently, the discovery of single‐atom dispersed catalyst (SAC) provides a new frontier in heterogeneous catalysis. However, the electrocatalytic application of SAC is still subject to several theoretical and experimental limitations. Further advances depend on a better design of SAC through optimizing its interaction with adsorbates during catalysis. Here, distinctive from previous studies, favorable 3d electronic occupation and enhanced metal–adsorbates interactions in single‐atom centers via the construction of nonplanar coordination is achieved, which is confirmed by advanced X‐ray spectroscopic and electrochemical studies. The as‐designed atomically dispersed cobalt sites within nonplanar coordination show significantly improved catalytic activity and selectivity toward the oxygen reduction reaction, approaching the benchmark Pt‐based catalysts. More importantly, the illustration of the active sites in SAC indicates metal‐natured catalytic sites and a media‐dependent catalytic pathway. Achieving structural and electronic engineering on SAC that promotes its catalytic performances provides a paradigm to bridge the gap between single‐atom catalysts design and electrocatalytic applications. Abstract : A paradigm of coordination design and electronic engineering of single‐atom dispersed cobalt catalysts (SAC) is demonstrated, which leads to significantly enhanced electrocatalytic activities and selectivity, therefore presenting new oxygen electrocatalysis pathways via achieving the favored site–adsorbate interactions, and the illustration of the active sites in SAC indicates the metal‐natured catalytic sites and a media‐dependent catalytic pathway.